Droplet impact on a concave wall in a rotating gas flow field. (June 2022) - Ouyang, Shuo; Xiong, Zhenqin; Zhao, Jiyun; Li, Zhen
Abstract: The behavior of liquid droplet impact on the concave wall in a rotating flow field is vital for swirl-vane separators and spiral fuel bundles in nuclear reactors. To reveal the collision mechanism of the droplet on the concave wall in a rotating flow field, a test rig for swirl vane separators is developed. The impacting behaviors of droplets on a concave wall with a diameter of 130 mm are recorded by a high-speed camera over wide ranges of diameters (0.2 mm < d < 4.0 mm) and the inlet gas velocities (2.7 m·s −1  < Vg, in  < 6.5 m·s −1 ). The trajectory and the velocity of the droplet before impact on the concave wall are obtained by numerical simulation. Four kinds of droplet impacting outcomes are observed, i.e., downward sliding spreading, horizontal shuttle sliding breaking, upward sliding breaking, and adhesion breaking. The distribution of these four patterns in Wer -Rer diagram is obtained and the correlations for predicting dividing lines are developed. Moreover, the effects of the inlet gas velocity and the droplet diameter on the droplet impacting location and the spreading factors are analyzed. The inlet gas velocity has the most significant effect on the droplet impact outcome and the spreading factors.